Synthesis of Alumina from aluminium can using dissolution process - Wan Roslina binti Wan Mohd (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
The increasing utilization of aluminum in daily life has produced a rise in aluminium scrap. At present, the method used to process aluminium scrap is smelting process which consumes high levels of energy and causes environmental problem. This research focuses on the development of an alternative technology to process waste aluminium can into high added value of products without releasing any waste materials. In this study, aluminium can was treated using an alkaline solution in a closed reactor. The aluminum dissolved easily in the solution and gas was spontaneously released. The results revealed that the process was mainly controlled by temperature and concentration. The higher the temperature and concentration, the faster the dissolution process and hydrogen generation. At the end of the process, the solution was filtrated and calcined at 800°C and 1000°C based on temperature that obtained from TG/DTA result. X-ray diffraction analysis confirmed that the filtrate sample was aluminium hydroxide, and the calcined filtrate contained of delta and theta alumina. Subsequently, particle size distribution showed that higher temperatures of calcination led to the production of finer alumina particles where the original filtrated sample had a particle size within the range of 30μm to 32μm while the calcined filtrate had a finer particle size within the range of 22μm to 23μm. On the other hand, the existence of hydrogen which was released during the dissolution process was verified through gas chromatography analysis. Energy analysis showed that there was no waste released throughout the process. Instead, the waste was utilized as the main source and converted into added value of products which was alumina powder and hydrogen gas by-products. Based on the results, the proposed process is efficient as it is environmentally safe, produces a green energy source and converts waste into valuable feedstock materials.